Antara Ali Yafie dan KH. Sahal Mahfudz: Perbandingan Pemikiran Fiqh Sosial dan Relevansinya dengan Indonesia Modern - Syihabuddin, Muhammad; Fauzie, Nadya Amri; Khasri, Muhammad Ilham Ulul Azmi (Pascasarjana UIN ANTASARI Banjarmasin, 2024)
This research compares the thinking of KH. Ali Yafie and KH. Sahal Mahfudz in the concept of social fiqh and its relevance to modern challenges in Indonesia. These two figures have a unique approach to formulating social fiqh: KH. Ali Yafie emphasized the harmony between traditional Islamic principles and the modern context, focusing on social, economic, and environmental justice, while KH. Sahal Mahfudz carries the method of